Infographic as a tool to Facilitate Teaching and Learning - Harun, Harrylmazrin; Shaari, Nassiriah; Othman, Azliza (2018)
This paper aims to review on how infographics can be used efficiently in education primarily as a teaching and learning tool. The term of infographic refers to the combination of information and graphics. Infographic is a medium to a representation of info and graphics that can communicate to diverse audiences, and the meaning can be understood quickly. Therefore, the application of infographics as data visualisation has a potential to be utilised in teaching and learning as a tool to facilitate the process of understanding the intended content.